An Analysis Of The Tongue Twister Technique Of Students Class of SMPN 1 Sitiung - Khairita, Martiya Nurni; Nanda, Dodi Widia; Hasanah, Hikmatul (Dharmas Education Journal (DE_Journal), 2025)
Teaching pronunciation skills in English is an important aspect that needs to be paid attention to in the learning process. Many students have difficulty pronouncing certain sounds, such as /r/, /l/, /θ/, and /ð/. Therefore, teachers need to apply methods that are engaging, interactive, and in accordance with the needs of students. One of the methods used in this study is the tongue twister game which is considered effective in practicing pronunciation in a fun way. This study aims to describe the application of the sound repetition game method in pronunciation learning in grade VII of SMPN 1 Sitiung and to identify its advantages and weaknesses. The approach used is qualitative descriptive with a case study design. The data collection technique was carried out through observation and interviews with teachers and students of grade VII for the 2025/2026 school year. The results of the study show that this method is applied gradually, starting from giving examples by teachers to taking turns reciting practice by students. The use of media in the form of text and pictures helps students' understanding. The students' responses showed increased confidence and pronunciation ability. The learning atmosphere became more active and fun. However, some challenges were also found, such as the need for longer time and there are still students who lack confidence when speaking in front of the class.Teaching pronunciation skills in English is an important aspect that needs to be paid attention to in the learning process. Many students have difficulty pronouncing certain sounds, such as /r/, /l/, /θ/, and /ð/. Therefore, teachers need to apply methods that are engaging, interactive, and in accordance with the needs of students. One of the methods used in this study is the tongue twister game which is considered effective in practicing pronunciation in a fun way.This study aims to describe the application of the sound repetition game method in pronunciation learning in grade VII of SMPN 1 Sitiung and to identify its advantages and weaknesses. The approach used is qualitative descriptive with a case study design. The data collection technique was carried out through observation and interviews with teachers and students of grade VII for the 2025/2026 school year.The results of the study show that this method is applied gradually, starting from giving examples by teachers to taking turns reciting practice by students. The use of media in the form of text and pictures helps students' understanding. The students' responses showed increased confidence and pronunciation ability. The learning atmosphere became more active and fun. However, some challenges were also found, such as the need for longer time and there are still students who lack confidence when speaking in front of the class.